Analisis Pembangunan Kawasan Perkotaan Di Kecamatan Gambut dan Kertak Hanyar Kabupaten Banjar - Noviana, Erika Roselma; Nur, Muhammad Anshar (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study intend to analyze the development of urban areas in Kecamatan Gambut and Kertak Hanyar Kabupaten Banjar. The research method using descriptive quantitative method. The results show that strategic location and support from government and private sector can be utilized for business and service development in Gambut and Kertak Hanyar sub-districts of Banjar Regency and make National Strategic Area (NSA)